2015
DOI: 10.1007/s11356-015-4808-9
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic biomineralization processes and Zn bioavailability: a synchrotron-based investigation of Pistacia lentiscus L. roots

Abstract: Plants growing on polluted soils need to control the bioavailability of pollutants to reduce their toxicity. This study aims to reveal processes occurring at the soil-root interface of Pistacia lentiscus L. growing on the highly Zn-contaminated tailings of Campo Pisano mine (SW Sardinia, Italy), in order to shed light on possible mechanisms allowing for plant adaptation. The study combines conventional X-ray diffraction (XRD) and scanning electron microscopy (SEM) with advanced synchrotron-based techniques, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 38 publications
3
34
1
1
Order By: Relevance
“…In this study, SEM and EDS analysis showed the presence of a mineral rim made up of Al-silicates coating the epidermis of H. tyrrhenicum roots (Figure 2), as previously observed in other autochthonous plant species growing in similar environments, like E. pithyusa subsp. cupanii, P. lentiscus, P. australis, and J. acutus [23,[76][77][78]109]. This structure was also detected by STXM ( Figure 6), also showing that Zn is mainly stored in the root epidermis.…”
Section: Mineral Rim At the Root-rhizosphere Interface And Zn Chemicamentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, SEM and EDS analysis showed the presence of a mineral rim made up of Al-silicates coating the epidermis of H. tyrrhenicum roots (Figure 2), as previously observed in other autochthonous plant species growing in similar environments, like E. pithyusa subsp. cupanii, P. lentiscus, P. australis, and J. acutus [23,[76][77][78]109]. This structure was also detected by STXM ( Figure 6), also showing that Zn is mainly stored in the root epidermis.…”
Section: Mineral Rim At the Root-rhizosphere Interface And Zn Chemicamentioning
confidence: 63%
“…XAS spectra for each sample were collected at least in triplicate for averaging and statistics. According to literature data [23,26,50,52,[74][75][76][77][78], in the soil-plant system, Zn can occur in different coordination environments, both bound to organic compounds (e.g., organic acids, phytochelatins, metallothioneins, etc.) and to inorganic molecules (e.g., sulfur, sulfate, carbonate, etc.)…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of both isotopic effects was larger than reported for hydroponically grown crops (Δ Znroot-solution -0.02 to 0.16‰, and Δ 66 Znshoot-root -0.25 to -0.56‰) (Weiss et al 2005;Jouvin et al 2012;Smolders et al 2013). Excess Zn can precipitate with insoluble phosphates or silicates at the root epidermis, the intercellular spaces, and the cell walls of the roots, a process termed biomineralization that might reduce Zn influx into the symplast (Neumann and zur Nieden 2001;Straczek et al 2008;Medas et al 2015;De Giudici et al 2015). In tobacco, Zn binds to the carboxyl and hydroxyl groups of pectin and to the hydroxyl groups of cellulose in the cell walls of roots (Straczek et al 2008).…”
Section: Zinc Allocation To the Seedsmentioning
confidence: 89%
“…Mineral and microscopic analysis in this work were conducted by X-ray Powder Diffraction (XRPD), Scanning Electron Microscopy (SEM), and synchrotron-based techniques such as X-ray Absorption Spectroscopy (XAS) and Scanning Transmission Xray Microscopy (STXM) [15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%